Notice the unnoticed - Nur'Aziean Abu Bakar (2016)
Being often engaged with our gadgets and other activities, we rarely take time to notice our surroundings because it's too common a sight to be observed and adored. This experimental project will translate our everyday occurrences into an art form by finding connections between creativity and everyday sight. By observing the unconscious and scrutinizing the unexamined, one can seek beauty in normality and discover the articulation of motion and time in space. This will allow them to take time to experience the passing present and embrace slowness.